Design and Performance Analysis of the WDM Schemes for Radio over Fiber System With Different Fiber Propagation Losses - Adnan Hussein Ali; Alaa Desher Farhood (Fibers, 2019)
The integration of optical and wireless networks increases mobility and capacity and decreases costs in access networks. Fibre optic communication can be considered optical communication that combines the methodologies of two communications, and it may be utilised in systems of wired and wireless communication. The solution for many problems is radio over fibre (RoF) because it can control many base stations (BS) that are connected to a central station (CS) with an optical fibre. The received RoF signal head for in a low quality; thus, many factors will result in some problems such as a high bit error rate (BER) and low Q-factor values, and the receiver might not be operating in a high data rate network. Wavelength division multiplexing (WDM) network can offer a solution to these problems where the transmission of different signals can be done with a single-mode fibre. BER should be reduced to assured values, and the Q-factor must be increased. The investigation of WDM-RoF with different lengths of fibre at various channel spacing will be simulated using Optisystem software, and the RoF’s receiver performance is measured and analyzed depending on the acquired BER, the value of the Q-factor, and the height of the opening of the eye diagram. The degradation factors effect such as attenuation and dispersion are significantly limited with the addition of an EDFA amplifier to a Single Mode Fibre (SMF).